Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/2041731418820034
|View full text |Cite
|
Sign up to set email alerts
|

Selectively activated PRP exerts differential effects on tendon stem/progenitor cells and tendon healing

Abstract: To understand the variable efficacy with platelet rich plasma (PRP) treatments for tendon injury, we determined the differential effects of proteinase-activated receptor (PAR)1- or PAR4-activated PRP (PAR1-PRP, PAR4-PRP) from humans on human patellar tendon stem/progenitor cells (TSCs) and tendon healing. We show that PAR1-PRP released VEGF, whereas PAR4-PRP released endostatin. Treatment of TSCs with PAR1-PRP increased collagen I expression and matrix metalloproteinase-1 (MMP-1), but cells treated with PAR4-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…It is believed that platelets, which contain and release numerous growth factors, promote healing, dampen inflammation, and reduce pain 3 5 . These blood-derived products have been used to enhance chondrogenesis 6 , 7 , treat bone 8 , 9 , tendon 10 , 11 and ligament 12 , 13 injuries, and have recently emerged as a potential therapeutic for knee OA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that platelets, which contain and release numerous growth factors, promote healing, dampen inflammation, and reduce pain 3 5 . These blood-derived products have been used to enhance chondrogenesis 6 , 7 , treat bone 8 , 9 , tendon 10 , 11 and ligament 12 , 13 injuries, and have recently emerged as a potential therapeutic for knee OA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that many growth factors including the human recombinant growth factors (eg, basic fibroblast growth factor, bFGF) 9,10 and the autogenous growth factors (eg, platelet‐rich plasma, PRP or platelet lysate, PL) 10‐12 have ability to affect the biology properties of MSCs. Among them, PRP or PL is a blood‐derived concentrate with a combination of growth factors, and has been confirmed to promote the proliferation and differentiation of stem cells 11‐13 . However, the products of PRP or PL display a number of disadvantages, and for instance, the preparation procedure is very complex and expensive, the composition may vary according to the different patients and preparation methods, and the mechanism and mainly responsible factors’ effect on stem cells have not been clear 10,13 .…”
Section: Introductionmentioning
confidence: 99%
“…77 Due to poor blood supply and limited self-renewal, injured tendons and ligaments heal slowly and incompletely. 78 The multistage healing procedure of cell proliferation and ECM production is slow and leads to the formation of collagenrich scar tissue with undesirable mechanical properties that make healed tendons susceptible to reinjury. 78 In addition, chronic pain, weakness, activity limitations, and loss of stamina 79 decrease the quality of life.…”
Section: In Ligament Muscle and Tendon Injurymentioning
confidence: 99%
“…Previous studies have demonstrated that activated PRP can stimulate the proliferation of TSCs and the production of tenocytes and abundant collagen. 78 Kim et al 80 investigated the therapeutic effect of bone marrow aspirate concentrates (BMACs) combined with PRP and tendon-derived stem cells (TDSCs) for rotator cuff tendon tears. The results indicated that the proliferation and migration of TDSCs were enhanced by the combination treatment and that the aberrant osteogenic and chondrogenic differentiation of TDSCs was prevented.…”
Section: In Ligament Muscle and Tendon Injurymentioning
confidence: 99%
See 1 more Smart Citation